A comparison between the squat and the deadlift for lower body strength and power training - Nigro, F.; Bartolomei, S. (Journal of Human Kinetics, 2020)
The aim of this study was to compare the effects of two resistance training programs including either a deadlift or a parallel squat on lower body maximal strength and power in resistance trained males. Twenty-five resistance trained men were randomly assigned to a deadlift group (DE; n = 14; age = 24.3 ± 4.1 y; body mass = 84.8 ± 14.2 kg; body height = 180.3 ± 6.8 cm) or to a squat group (SQ; n = 11; age = 22.3 ± 1.6 y; body mass = 83.0 ± 13.6 kg; body height 179.9 ± 6.1 cm). Both groups trained 3 times per week for 6 weeks. The deadlift and the squat were the only lower body maximal strength exercises performed by DE and SQ groups, respectively, while both training programs included jumps. A significantly (p = 0.017) greater increase in deadlift 1RM was observed in the DE compared to the SQ group, while the SQ group obtained a significantly (p = 0.049) greater increase in squat 1RM. A significant increase in jump performance (p = 0.010), without significant interactions between groups (p = 0.552), was observed in both groups. Three participants of the DE group developed lower back pain and were excluded from the study. Results indicate that both the squat and the deadlift can result in similar improvement in lower body maximal strength and jump performance and can be successfully included in strength training programs. The incidence of back pain in the DE group may suggest a marked stress of this exercise on the lower back. Proper technique should be used to minimize the risk of injury, especially when the deadlift is performed.